2014
DOI: 10.2174/09298665113209990077
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Protein Unfolding with Solid-state Nanopores

Abstract: In this work, we review the process of protein unfolding characterized by a solid-state nanopore based device. The occupied or excluded volume of a protein molecule in a nanopore depends on the protein’s conformation or shape. A folded protein has a larger excluded volume in a nanopore thus it blocks more ionic current flow than its unfolded form and produces a greater current blockage amplitude. The time duration a protein stays in a pore also depends on the protein’s folding state. We use Bovine Serum Albumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 42 publications
4
55
0
Order By: Relevance
“…In a previous study, Li and colleagues made a survey of different denaturants that facilitate the translocation of unfolded proteins through nanopores. 28 However, no detailed study has been reported on the use of SDS for nanopore translocation of proteins. More recently, Kennedy et al used SDS to translocate proteins through a sub-nanometer pore, however, no information on the detergent-protein interaction is provided.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, Li and colleagues made a survey of different denaturants that facilitate the translocation of unfolded proteins through nanopores. 28 However, no detailed study has been reported on the use of SDS for nanopore translocation of proteins. More recently, Kennedy et al used SDS to translocate proteins through a sub-nanometer pore, however, no information on the detergent-protein interaction is provided.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely due to the heterogeneous charge structure of the GCN4-p1 amino acid sequence ( Figure 1D). Solid-state nanopore induced protein denaturation has been studied elsewhere, 3,25,40,41 and could explain the shift away from larger amplitude (ΔI) events at high voltages. In particular, dimers have a larger excluded volume within the pore than monomers.…”
Section: Resultsmentioning
confidence: 99%
“…We interpret these blockades as a temperaturebased unfolding of the GCN4-p1 dimer into its monomer form. 9,10,22,25,44,46 Temperature-based unfolding will expose hydrophobic leucines. Similar hydrophobic exposure has been shown to drive adsorption of protein Note the appearance of long-lived (>5 ms) half-amplitude events at room temperature.…”
Section: Articlementioning
confidence: 99%
“…A biased voltage is applied across a thin membrane containing a nanopore, resulting in an ionic current from one cell to another [25]. Protein molecules including folded and unfolded structures are detected and analyzed by solid-state nanopore [2629]. The interaction of proteins can also be detected using solid-state nanopore [30, 31].…”
Section: Introductionmentioning
confidence: 99%